A Giant Sialolith Consisted of Tooth-like Tissue in the Duct of Submandibular Gland - Jung, Tae Young (The Korean Journal of Oral and Maxillofacial Pathology, 2020)
A 20-year-old woman who had a main symptom of intermittent pain in both mandibular third molar visited our hospital. In CBCT findings, the #38, 48 teeth were located on the lingual side of the inferior alveolar nerve. In addition, a large stone about 12mm in length was observed in the right Wharton's duct in CBCT findings. Neck CT scan was performed and a large stone about 12mm in length was observed, and the accumulation of saliva in the rear of the stone was observed. The patient underwent sialolithotomy and #38, 48 tooth extraction through intraoral approach under general anesthesia. The removed stone was similar in shape and color to a tooth. The removed stone was markedly fragmented and composed of dentin and enamel-like tissue which showed lamellate arrangement in microscopic examination. Patient was presently symptom free after 10months postoperatively KCI Citation Count: 0